2022
DOI: 10.1038/s41598-022-08400-z
|View full text |Cite
|
Sign up to set email alerts
|

Conventional GnRH antagonist protocols versus long GnRH agonist protocol in IVF/ICSI cycles of polycystic ovary syndrome women: a systematic review and meta-analysis

Abstract: Gonadotropin-releasing hormone (GnRH) analogues are commonly used in clinical practice to prevent premature luteinizing hormone (LH) surge during In-Vitro Fertilization/ Intra-Cytoplasmic Sperm Injection (IVF/ICSI) cycles. This review aimed to summarize the available evidence comparing the effects of conventional GnRH antagonist protocols, the most commonly used GnRH antagonist protocols, and GnRH agonist protocols on IVF/ICSI outcomes in women with polycystic ovary syndrome (PCOS). A comprehensive electronic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 82 publications
0
30
0
Order By: Relevance
“…The conventional long protocol of ovarian stimulation for IVF-embryo transfer is based upon the administration of exogenous Gn combined with GnRHa. The aim of using GnRHa is to prevent the premature rise of LH due to positive feedback by the high serum concentration of estradiol[ 13 - 15 ]. The use of GnRHa is associated with an increased incidence of functional ovarian cysts; this may be the effect of the “flare-up” phenomenon of GnRHa.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional long protocol of ovarian stimulation for IVF-embryo transfer is based upon the administration of exogenous Gn combined with GnRHa. The aim of using GnRHa is to prevent the premature rise of LH due to positive feedback by the high serum concentration of estradiol[ 13 - 15 ]. The use of GnRHa is associated with an increased incidence of functional ovarian cysts; this may be the effect of the “flare-up” phenomenon of GnRHa.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition gonadotropin reduces AMH expression from granulosa cells of early-preantral follicles of the marmoset ovary [63] while treating human granulosa cells obtained from the follicular uid samples of IVF/ICSI cycles with FSH represses AMH expression which explain the negative correlation between the FF AMH and the total FSH dose that was observed in the current study. However, the lower gonadotropin requirements [65] during the GnRH antagonist protocol might hinder the correlation from reaching signi cance levels in the PCOS-Anta group. Similarly, we noted signi cantly negative correlations between the FF AMH levels and the number of retrieved oocytes, MII oocytes, MI oocytes, GV oocytes, immature oocytes, fertilized oocytes, and the number of obtained embryos in the PCOS-A group only.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis including 10 studies and 1214 women comparing GnRH agonist to antagonist protocols in PCOS patients confirmed the findings of similar pregnancy outcomes for agonist and antagonist protocols. They also found that antagonist protocols had a significantly lower rate of OHSS, lower gonadotropin consumption, and shorter duration of stimulation [16]. All patients in the included studies had been on combined oral contraceptive (COC) for at least 21 days prior to stimulation start.…”
Section: Key Pointsmentioning
confidence: 98%